Conceptualising In-Flight Experience: An air Traveller Perspective - Claire Ng; Isaac Henderson (Centre For Tourism Planning and Development, 2021)
The aviation industry has evolved rapidly in recent years, and so have consumer expectations with regard to air travel. This study examines how air travellers conceptualise in-flight experience. Using a mixed-methods approach, this study is divided into two phases. First, semi-structured qualitative interviews were undertaken with 32 members of the flying public and analysed using thematic analysis. Second, based upon the key themes identified in the first phase, a questionnaire (with both quantitative and qualitative questions) was developed and administered to 151 participants. The first phase identified the different ways air travellers conceptualise in-flight experience, with the most important elements being food and drinks, flight attendants, entertainment, seat comfort, and leg room. In the second phase these important elements are shown to have statistically significant effects upon in-flight experience (using a t-test and chi-squared goodness of fit test), however, the size of their effects varied. A Friedman test (with post-hoc Wilcoxon signed-rank test) demonstrates that air travellers rank the contribution of each of these elements towards in-flight experience differently. The findings allow airline managers to prioritise different aspects of in-flight experience based upon their relative importance to air travellers.